Nondestructive characterization of materials IV - International Symposium on Nondestructive Characterization of Materials (4th : 1990 : Annapolis, Maryland); Ruud, Clayton O.; Bussiere, Jean F.; Green, Robert E. (New York : Plenum Press, 1991)
09